A bateria de Edu Ribeiro em Cebola no Frevo: a performance de uma mesma obra em diferentes contextos - Otho Guimarães Filho (2024)
This research seeks to investigate how one drummer may perform the same song in different contexts. What remains the same and what changes in the interpretation of the drum part? To this end, we chose a case study of drummer Edu Ribeiro performing versions of the song Cebola no Frevo in different formations between 2006 (first recording of the song) and 2022 (beginning of this research). The performance analysis considersthree aspects: the construction of the drum line for the song's theme, the accompaniment of soloists, and the drummer's improvisation solo. To assist the process of analysis, it was necessary to dialogue with the existing bibliography on drum performance and Brazilian drums (and on Edu Ribeiro himself), with interviews and classes with Ribeiro, and with concepts such as transcription, musical interaction, and style. Twelve versions of the song were found, several of these versions transcribed and analyzed. Among the main results, the following approaches stand out: Edu performs a drum line in the song's theme, very well defined and recurring in terms of structure and phrasing, in which it is understood that there is a composition for this line; there are recurrences of structural ideas and phrasing/motifs both in the accompaniment of other soloists and in the drum solo. The recurring structure of the song allowed the construction of a general map of the song that presents the main ideas present among the versions found.